Effect of farming system on meat traits of native Massese suckling lamb. Issue 1 (1st January 2021) - Parrini, Silvia; Sirtori, Francesco; Acciaioli, Anna; Becciolini, Valentina; Crovetti, Alessandro; Bonelli, Antonio; Franci, Oreste; Bozzi, Riccardo
Abstract: Growth performance and meat quality traits of 24 Massese suckling lambs reared up to 69 days of age in different farming systems were evaluated. Three groups were considered: stall (S) reared indoors and fed concentrate and hay; pasture (P) reared outdoor and fed pasture and hay; semi free-range (F) reared indoors during the night and at pasture during the day, fed concentrate, hay and herbage. The lambs remained constantly with their dams for the whole period, having thus always access to mothers' milk. Animals weights were recorded, and, after slaughtering, carcase traits were considered. Fatty acids composition and chemical/physical parameters of milk and meat were analysed. Lambs growth was similar in the first 30 days, while afterwards differences emerged: P lambs recorded the worst values reaching slaughter weight of 14.6 kg versus 22.3 and 22.7 of the S and the F group, respectively. Carcase of P lambs resulted less fat and with a lower lean/bone ratio than the other groups (1.8, 2.1 and 2.3 for P, S and F, respectively). Fatty acids composition of ewes' milk had effect on lambs' meat profile, probably because they continued to suck milk until slaughter. Moreover, also farming system affected fatty acids profile of lambs' meat: grazing animals, especially P, showed the highest PUFA and the lowest SFA percentage and P meat showed the best composition for human health. As regards physical traits, F meat was more coloured than P and S meat, while P meat was less tender than others. Highlights: Two-month-old Massese lamb is a marketable product. Suckled milk affected lambs' meat composition also at later ages. Pasture in lambs' diet increases PUFA content in the meat.